2018
DOI: 10.1080/15532739.2018.1428842
|View full text |Cite
|
Sign up to set email alerts
|

First impressions online: The inclusion of transgender and gender nonconforming identities and services in mental healthcare providers' online materials in the USA

Abstract: Background: When accessing mental healthcare services, transgender and gender nonconforming (TGNC) individuals face systemic barriers to gender-affirmative care. Initial points of contact, like intake forms, may show limited consideration for the heterogeneity of TGNC identities and can lead to negative consequences prior to face-to-face interaction with providers. Aims: The first aim was to mimic a likely pathway a TGNC individual may follow to seek mental healthcare services in the USA and to describe the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Community participants in our interviews identified that markers of stigma and lack of support in the waiting room, paperwork, and initial encounters with a clinician or support staff often act as barriers to care or cause stress and anxiety. For example, a binary option for gender on intake paperwork conveys a stigmatizing message, whereas a blank space for specifying gender and the name you wish to be called allows maximum flexibility for a wide variety of gender identities and individual situations (Holt et al, 2019; Puckett et al, 2020). Another option is to defer discussion of these identity markers until in the privacy of the therapy room.…”
Section: Trans Collaborations Practice Adaptations For Psychological ...mentioning
confidence: 99%
“…Community participants in our interviews identified that markers of stigma and lack of support in the waiting room, paperwork, and initial encounters with a clinician or support staff often act as barriers to care or cause stress and anxiety. For example, a binary option for gender on intake paperwork conveys a stigmatizing message, whereas a blank space for specifying gender and the name you wish to be called allows maximum flexibility for a wide variety of gender identities and individual situations (Holt et al, 2019; Puckett et al, 2020). Another option is to defer discussion of these identity markers until in the privacy of the therapy room.…”
Section: Trans Collaborations Practice Adaptations For Psychological ...mentioning
confidence: 99%
“…Most research and recommendations have focused on how to provide affirming care to TGNB patients via patient–provider interactions, such as affirming pronoun use, affirming options on paperwork, and affirming clinical interviewing skills (American Psychological Association [APA], 2015; Hagen & Galupo, 2014; McPhail et al, 2016). Though some nascent work has addressed how affirmation of TGNB individuals begins even before the clinical encounter, when patients are seeking out providers (Holt et al, 2019). The aim of the current project was to extend UX research to UX of TGNB affirmation of mental health care provider webpages, focusing on the UX of websites from the perspectives of both TGNB and cisgender individuals.…”
Section: Does Inclusivity Cost Patients?mentioning
confidence: 99%
“…The term transgender occurred on only 32% of the sites that had any LGBT-inclusive wording. In an analysis of websites for medical and behavioral health providers who were on the World Professional Association for Transgender Health provider finder page (Holt et al, 2019), a total of 527 websites were reviewed, along with 114 online intake forms for the providers. Trans-inclusive language was present in only 54% of intake forms; only 18% of intake forms provided a pronoun question and only 33% had a specific space for patients to enter a name different from their legal name.…”
Section: Does Inclusivity Cost Patients?mentioning
confidence: 99%
See 1 more Smart Citation
“…Access to health insurance is a known barrier, well documented in the United States [34] but also relevant in the Australian context, as a dearth of publicly funded options for medical gender affirmation diminish access among those without privately funded insurance coverage [35]. The intake paperwork, registration processes, and electronic medical record systems used by many health services often reproduce rigid categories of binary gender and confusion between patient gender, physical characteristics, and gender presumed at birth [36][37][38]. Many clinics fail to provide gender neutral bathrooms, which is a significant source of concern for many trans people [39] and part of broader organizational tensions that arise through gender segregation in health settings and an overall failure to spatially configure health spaces in ways that are affirming, confidential, and safe for trans patients [40,41].…”
Section: Introductionmentioning
confidence: 99%